Genetic diversity and population structure of Penicillium roqueforti isolates from Turkish blue cheeses - Kirtil, Hatice Ebrar; Orakci, Aysenur; Arici, Muhammet; Metin, Banu (ELSEVIER, 2024)
Blue cheeses, including renowned mold-ripened varieties such as Roquefort (France), Gorgonzola (Italy), Stilton (UK), Danablue (Denmark), and Cabrales (Spain), owe their distinct blue-green color and unique flavor to the fungal species Penicillium roqueforti. In Turkey, traditional cheeses similar to blue cheeses, namely mold-ripened Tulum and Civil, employ production techniques distinct from their European counterparts. Notably, moldripening in Turkish cheeses is spontaneous and does not involve starter cultures. Despite P. roqueforti being recognized for its distinct genetic populations sourced from various blue cheeses and non-cheese origins globally, the characteristics of the P. roqueforti population within Turkish cheeses remain unexplored. This study aimed to unravel the genetic characteristics and population structure of P. roqueforti from Turkish mold-ripened cheeses. Analysis of mold-ripened Civil (n = 22) and Tulum (n = 8) samples revealed 66 P. roqueforti isolates (76.6 % of total fungal isolates). Subsequently, these isolates (n = 66) and those from previous studies (Tulum n = 53, Golot n = 1) were used to assess genetic characteristics and mating genotypes. All 120 isolates harbored horizontal transfer regions (Wallaby and CheesyTer) and predominantly possessed the MAT1-2 mating genotype, similar to global blue cheese populations. However, most lacked the mpaC deletion associated with such populations. Analysis of the population with three polymorphic microsatellite markers revealed 36 haplotypes (HTs). Some cheeses contained isolates with different HTs or opposite mating genotypes, aligning with spontaneous fungal growth. Tulum and Civil isolates exhibited similar population diversity without forming distinct subgroups. Phylogenetic analysis of 20 selected isolates showed 75 % aligning with global blue cheese isolates, while 25 % formed unique clades. Overall, Turkish P. roqueforti isolates share genetic similarities with global populations but exhibit unique characteristics, suggesting potential new clades deserving further investigation. This research illuminates the characteristics of P. roqueforti isolates from Turkish cheeses, contributing to the knowledge of the global intraspecific diversity of the P. roqueforti species.
Keywords: Filamentous fungi; Mating type; Mold-ripened cheese; mpaC; Haplotype; IDENTIFICATION; MICROBIOTA; SOFTWARE; CLUSTERS; NUMBER; Food Science & Technology; Microbiology